Outcomes after Vena Cava Filter Use in Patients with Cancer-Associated Venous Thromboembolism and Contraindications to Anticoagulation - Quezada, Andrés; Jiménez, David; Bikdeli, Behnood; Muriel, Alfonso; Aramberri, Mario; López-Jiménez, Luciano; Sahuquillo, Joan Carles; Otero, Remedios; Porfidia, Angelo; Monreal, Manuel; RIETE Investigators; Bosevski, Marijan; et al. (Georg Thieme Verlag KG, 2020)
The association between the use of inferior vena cava filters (IVCFs) and outcomes among patients with cancer-associated thromboembolism (CT) and contraindications to anticoagulation remains unclear.